The dynamics of importer–exporter connections - Victor Gimenez-Perales (European Economic Review, 2024)
This paper studies the dynamics of importer–exporter connections when importers source inputs from multiple exporters. I first develop a trade model in which heterogeneous importers invest in expanding the set of potential exporters they know and from which they can source. The model delivers three novel predictions. The lower the degree of substitutability among final goods and the higher the degree of substitutability among inputs of an importer: (i) the lower the growth rate in importer's connections, (ii) the more likely are connections to be discontinued, and (iii) the lower the trade value growth per surviving connection. I then provide evidence in favor of these predictions by using customs transaction data from Colombia. Finally, I show that the mechanism unveiled in this paper matters for the heterogeneity of the trade adjustment to macroeconomic shocks across sectors.
Keywords: D21; F10; F14; F23; L14; 330; Importers; Survival; Connections; Dynamic model